KAJIAN BESARAN RUANG PADA UNIT RUMAH SUSUN DI JAKARTA, Studi Kasus: Rusun Tebet, Rusun Tanah Abang dan Rusunami Kalibata - Susy Irma Adisurya (Jurnal Dimensi Seni Rupa dan Desain, 2016)
AbstractThe 22nd Presidential Decree of 2006 on the coordination of Housing Development Planning in Urban Area (PPRSKP Coordination Team) has turned the existence of a terraced house (vertical housing) into a housing solution for the over population in big cities. Simple flats (RUSUNA), according to the government is measures by 18 m2, 25 m2 and 36 m2. Ownership of this unit will not automatically in the tax subsidies by the government and the developer. This is in accordance with the regulations of Government Regulation No.31 of 2007, provides consumers with a VAT exemption on certain conditions.Government of DKI Jakarta during the time of governor Jokowi had a program of development of the Flats as an effort to fulfill the housing needs of the people who inhabited the slums of Jakarta. As many of the towers with adequately spaced units arevery limited, they don't comply with the minimum necessities for a single family. Therefore, it is necessary to further research on the space of residential units in this Flat. This study will look at the extent of the influence of relationships between activityand unit size. Does the size of residential units in the towers are in accordance with the needs of users, of which the majority are lower middle class people who are married and have children? With a hybrid of qualitative and quantitative research methods,researchers conducted observations and data collection on simple towers of residential units in the area of Tanah Abang, Tebet and Kalibata. Results of the analysis showed that it can be concluded that some of the size of each room in a residential unit towers built in the 80s, 90s and 2000s already fulfilled thestandards of housing needs, but some of them don't. Results of this study was proposed to be practical reference that can be used as a guide by the Jakarta City Administration and the Department of Public Works (MPW), the developer of flats in Indonesia and the general public in need.AbstrakKeputusan Presiden No.22 Tahun 2006 tentang koordinasi Perencanaan Pembangunan Rumah di Kawasan Perkotaan (Tim Koordinasi PPRSKP) membuat keberadaan rumah bertingkat (vertical housing) menjadi solusi bagi pemenuhan perumahan penduduk di kota besar. Rumah Susun Sederhana (RUSUNA) menurut pemerintah adalah berukuran 18 m2, 25 m2, dan 36 m2. Kepemilikan unit ini otomatis tidak akan di subsidi pajaknya oleh pemerintah dan pihak pengembang. Hal ini sesuai dengan peraturan Peraturan Pemerintah No.31 Tahun 2007, berisi pembebasan PPN pada konsumen dengan syarat-syarat tertentu. Pemerintahan DKI Jakarta di masa gubernur Jokowi memiliki program pembangunan Rumah Susun sebagai upaya pemenuhan kebutuhan perumahan rakyat. Kelak penghuninya adalah masyarakat dari daerah kumuh di Jakarta, karena banyak dari Rusun yang ada besaran luas unitnya sangat terbatas, tidak sesuai dengan kebutuhan minimal untuk satu keluarga sederhana. Perlu diadakan penelitian lebih mendalam tentang besar luasan unit hunian Rusun ini. Dalam penelitian dilihat sejauh mana pengaruh hubungan aktifitas dengan besar unit hunian. Apakah ukuran unit hunian di rusun sudah sesuai dengan kebutuhan penggunanya, yang mayoritas adalahmasyarakat kelas menengah bawah yang sudah berkeluarga dan memiliki anak. Dengan metode penelitian campuran antara kualitatif dengan kuantitatif peneliti melakukan observasi dan pendataan terhadap unit hunian rusun sederhana di wilayah Tanah Abang, Tebet dan Kalibata. Hasil analisis menunjukan bahwa melalui analisa di atas dapat disimpulkanbahwa ukuran tiap ruang dalam unit hunian Rusun yang dibangun tahun 80an, 90an dan 2000an ada yang sudah sesuai dan ada yg belum sesuai dengan kebutuhan penggunanya. Hasil penelitian ini diusulkan menjadi acuan praktis yang dapat dijadikan panduan oleh Pemerintah Daerah DKI Jakartadan Departemen Pekerjaan Umum (DPU), para pengembang rumah susun di indonesia dan masyarakat umum yang memerlukan.